2020
DOI: 10.1155/2020/8833973
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Methicillin-ResistantStaphylococcus aureus(MRSA) from Milk in Shire Dairy Farms, Tigray, Ethiopia

Abstract: Antibiotic-resistant Staphylococcus aureus isolates pose a severe challenge to both veterinary and health professions and dairy cattle producers. Cross-sectional study was conducted from November 2014 to May 2015 to isolate and identify S. aureus from mastitic cows’ milk and estimate the occurrence of MRSA in the dairy farms of Shire. Physical examination and California mastitis test were performed on a total of 220 dairy cows. Bacteriological isolation and identification and antibiogram testing were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 42 publications
2
17
5
Order By: Relevance
“…It is comparable with a study reported at Alage Veterinary College Dairy Farm 21.2%, 17 Uganda 20.3% 8 and China 22.3%. 26 However, our result is lower than the prevalence conducted in Addis Ababa 50%, 9 Hawassa 51.2%, 27 Bishoftu 28.65%, 28 Hawassa 78%, 29 Mekele 32.81%, 30 China 46.2%, 31 Italy 47.2% 13 and India 54.3%. 32 These variations might be the different in management system used by the farm, types of sample for example in Italy bulk tank milk and in Hawassa 29 only milk sample was analyzed, diagnostic test like PCR test was used for a studies in Mekele and India.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…It is comparable with a study reported at Alage Veterinary College Dairy Farm 21.2%, 17 Uganda 20.3% 8 and China 22.3%. 26 However, our result is lower than the prevalence conducted in Addis Ababa 50%, 9 Hawassa 51.2%, 27 Bishoftu 28.65%, 28 Hawassa 78%, 29 Mekele 32.81%, 30 China 46.2%, 31 Italy 47.2% 13 and India 54.3%. 32 These variations might be the different in management system used by the farm, types of sample for example in Italy bulk tank milk and in Hawassa 29 only milk sample was analyzed, diagnostic test like PCR test was used for a studies in Mekele and India.…”
Section: Discussioncontrasting
confidence: 77%
“…The prevalence of S. aureus from cow milk in this study 25.53% was higher than the study conducted in Mukaturi and Sululta 15.3%, 14 but lower than Tigray 38.09%. 30 This is due to variation in hygienic procedure, sample size and variation in clinical cases for example in a study conducted in Tigray all study subjects had mastitis. On the other hand, the isolation rate of S. aureus in milkers’ hand swabs and udder swabs was also (19.2%) and (10%) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, seven S. aureus isolates were resistant to Oxacillin, but did not carry a mecA gene, which supports the findings of this study [ 18 ]. However, in a study conducted in four provinces of China, 47.6%(49/103) of S. aureus isolates from milk samples were identified as MRSA with the mecA gene [ 19 ], which is significantly higher than isolated in this study and other studies in the region [ 19 , 20 ]. MRSA carrying the mecA gene has been found in varying proportions in different parts of the world, for example, 42.9% ( n = 64) in Tigray, Ethiopia [ 20 ], 35.7% ( n = 84) in Egypt [ 21 ], 9% ( n = 728) in Karnataka, India [ 22 ], 0.8% ( n = 363) in bulk milk tanks in England and Wales [ 23 ].…”
Section: Discussionmentioning
confidence: 56%
“…The S. aureus and CoNS isolates were found to be relatively sensitive to Tetracycline and Cefazolin. In a study conducted in Ethiopia, isolates were highly resistant to Ampicillin, but were sensitive to Amikacin, Gentamycin, and Tetracycline [ 20 ]. A high level of MDR S. aureus was also found in several other studies [ 17 , 18 , 20 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation